Learning Space Transformation: An Innovation Design in the Computer Laboratory - Ahmad, Eka Maulana; Kaharuddin, Kaharuddin; Jufriadi, Jufriadi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2023)
This research aims to develop an interior design plan for the computer laboratory at SMKN 1 North Luwu. The research methodology employed in this study is research and development (R&D). The research process consists of several steps, including analyzing potential issues and challenges, accomplished through an extensive review of existing literature and on-site field studies. Data is collected through methods, including observations, interviews, and documentation. The content of the design development encompasses several crucial aspects. First, it involves the creation of a design concept for the laboratory, which is then translated into detailed 2D working drawings and 3D perspective drawings. These design proposals are rigorously assessed and validated by experts and practitioners. The outcomes of this research effort include a comprehensive interior design plan tailored specifically for the computer laboratory at SMKN 1 North Luwu. This design plan is presented through detailed 2D drawings and 3D modeling using V-ray SketchUp 2020. The validation process of the design resulted in a score of 141 with a percentage of 97.9%, indicating that the product design is highly suitable as an exemplary model for managing the computer laboratory at SMKN 1 North Luwu, with a classification of